The fire station - Munsch, Robert N., 1945- (Toronto : Annick Press, 1991)
Two young children explore a fire station and suddenly find themselves in the back of a fire truck as it races to a fire.
460
Accelerated Reader AR
Keywords: Fire departments -- Fiction; Fires -- Fiction; Fire fighters -- Fiction